Optimalisasi Literasi Keuangan Dalam Pencegahan Pinjaman Online Ilegal pada Usaha Mikro Kecil dan Menengah (UMKM) - Srirejeki, Kiky; Roesiana, Monica; Luhita, Tiladela; Khairurrizqo, Khairurrizqo (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
The objective of this financial literacy outreach program is to prevent micro, small, and medium enterprises (MSMEs) from getting trapped in illegal online loans. Data indicates a significant increase in the number of individuals involved in online loans, underscoring the critical importance of this initiative. The program encompasses educational sessions designed to equip participants with the skills to distinguish between legal and illegal online loan providers. Furthermore, the program includes preventive measures and provides comprehensive guidelines on steps to take if participants are already involved with illegal online loans. This initiative aims to foster a more sustainable and secure financial ecosystem for MSMEs in Banyumas Regency.